Effect of Sodium Ascorbate and the Time Lapse before Cementation after Internal Bleaching on Bond Strength between Dentin and Ceramic - May, Liliana G.; Salvia, Ana C. R. [UNESP]; Souza, Rodrigo O. A.; Michida, Silvia M. A. [UNESP]; Valera, Marcia C. [UNESP]; Takahashi, Fernando Eidi [UNESP]; Bottino, Marco Antonio [UNESP] (Wiley-Blackwell, 2010)
Purpose: To evaluate the effects of the elapsed time (ET) after nonvital bleaching (NVB) and sodium ascorbate application (10%) (SAA) on the shear bond strength of dentin to ceramic.Materials and Methods: Bovine incisors were selected, internally bleached (35% carbamide peroxide) for 9 days and submitted to the following treatments (n = 10): G1, G2, G3-luting after 1, 7, and 14 days; G4, G5, and G6-luting after SAA, 1, 7, and 14 days, respectively. G7 and G8 were not bleached: G7-luting 24 hours after access cavity sealing; G8-luting 24 hours after access cavity sealing after SAA. After NVB, the vestibular dentin was exposed and flattened. The SAA was applied to the dentin (G4, G5, G6, G8) for 10 minutes, and it was then washed and dried. The dentin was etched (37% phosphoric acid), and an adhesive system (Single Bond 2) was applied. Feldspathic ceramic discs (VM7; 4-mm diameter, 3-mm thick) were luted with a dual-resin agent (RelyX ARC, 3M ESPE Dental Products, St. Paul, MN). After 24 hours, specimens were submitted to shear test on a universal testing machine. The data (MPa) were submitted to ANOVA and Dunnet's test (5%).Results: The means (+/- SD) obtained were (MPa): G1 (14 +/- 4.5), G2 (14.6 +/- 3.1), G3 (14 +/- 3.7), G4 (15.5 +/- 4.6), G5 (19.87 +/- 4.5), G6 (16.5 +/- 3.7), G7 (22.8 +/- 6.2), and G8 (18.9 +/- 5.4). SAA had a significant effect on bond strength (p = 0.0054). The effect of ET was not significant (p = 0.1519). G5 and G6 presented higher values than the other bleached groups (p < 0.05) and similar to G7 and G8 (p > 0.05).Conclusions: After NVB, adhesive luting to dentin is recommended after 7 days if sodium ascorbate has been applied prior to dentin hybridization.
Keywords: Nonvital bleaching; elapsed time; sodium ascorbate; shear bond strength